2008
DOI: 10.1111/j.1468-2982.2007.01491.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topiramate on Migraine Frequency and Cortical Excitability in Patients with Frequent Migraine

Abstract: We studied the excitability of the visual and motor cortex in 36 patients with frequent migraine without aura (30 women, mean age 38.6 +/- 10.0 years) before and after treatment with topiramate (100 mg/day) using transcranial magnetic stimulation. Treatment with topiramate resulted in reduction of both headache frequency (12.0 +/- 1.3 to 5.8 +/- 3.2 migraine days per month; P = 0.004) and cortical excitability: motor cortex thresholds increased on the right side from 43.8 +/- 7.5% to 47.7 +/- 9.2% (P = 0.049) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…This is consistent with a previous study showing that the anticonvulsant drug topiramate may reduce migraine headaches. 24 However, the drug did cause a headache in one of our patients, a result consistent with the findings of Piovesan et al 25 There are several potential limitations of this study. Firstly, this paper is only a descriptive case series and not a randomised controlled trial.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with a previous study showing that the anticonvulsant drug topiramate may reduce migraine headaches. 24 However, the drug did cause a headache in one of our patients, a result consistent with the findings of Piovesan et al 25 There are several potential limitations of this study. Firstly, this paper is only a descriptive case series and not a randomised controlled trial.…”
Section: Discussionsupporting
confidence: 85%
“…In an open label trial with levetiracetam change of headache frequency and change of PT were negatively correlated at the 10% but not at the 5% significance level [25]. Mean PT were also increased following preventive treatment with topiramate in patients with migraine without aura [24]. Surprisingly, an inverse correlation was reported between decrease of migraine frequency and increase of mean PT.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of previous studies and the present data suggest that migraine prophylaxis with different centrally acting substances may be more complex and cannot only be explained by modification of cortical excitability. A non-linear relation between migraine activity and PT in patients with frequent migraine has also been discussed [24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preventive treatment for migraine which is essentially the same for patients with or without aura, has modulatory role on excitability of the cerebral cortex. Neurophysiological studies demonstrated that the cortical hyper-responsivity in migraine patients seemed to be normalized during preventive medication, in parallel to clinical improvement (Artemenko et al 2008;Mulleners et al 2002;Schoenen et al 1986). The application of cathodal stimulation over the occipital cortex could play a role with regard to pain control in migraine (Antal et al 2011).…”
Section: Effective Preventive Medications Modulate Cortical Excitabilitymentioning
confidence: 96%